The Legal Standing and Protection of Leasehold Rights within the Insolvency Estate under Law No. 37 of 2004: A Case Study of PT New Nordic Indonesia’s Bankruptcy - Putu Sunari Asih; I Made Deddy Priyanto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study analyzes the legal standing and implications of lease rights within the framework of bankruptcy proceedings in Indonesia, specifically focusing on the PT New Nordic Indonesia case. Although lease rights are theoretically categorized as personal rights (persoonlijk recht) under the Indonesian Civil Code (KUHPerdata), in modern property industries, they function as high-value economic assets. The primary conflict arises when a debtor’s insolvency disrupts ongoing lease agreements, pitting the Curator’s mandate to maximize the bankruptcy estate (boedel pailit) against the lessee’s right of enjoyment. Using a normative legal research method, this study examines the synchronization between KUHPerdata and Law No. 37 of 2004 (UU KPKPU). The findings indicate that while Article 36 and Article 38 of the UU KPKPU grant Curators discretionary authority to terminate or continue reciprocal agreements, this power is strictly limited by Article 38 Paragraph (3). This provision provides crucial legal protection for lessees—often investors—who have paid rent in advance, ensuring their right to occupy or utilize the asset remains guaranteed despite the owner’s bankruptcy. In the PT New Nordic Indonesia case, the implementation of these provisions is complicated by complex investment schemes involving